Prevalence, risk factors and psychological consequences of workplace violence among health workers in the Greater Accra region, Ghana: a cross-sectional study - Philip Apraku Tawiah; Emmanuel Appiah-Brempong; Paul Okyere; Geoffrey Adu-Fosu; Mary Eyram Ashinyo (BMC, 2024)
Abstract Background Globally, close to one-third of all workplace violence (WV) occurs in the health sector. Exposure to WV among healthcare professionals in Ghana has been widely speculated, but there is limited evidence on the problem. This study therefore investigated WV, its risk factors, and the psychological consequences experienced by health workers in Ghana. Methods An analytic cross-sectional study was conducted in the Greater Accra region from January 30 to May 31, 2023, involving selected health facilities. The participants for the study were selected using a simple random sampling technique based on probability proportional-to-size. The data analyses were performed using STATA 15 software. Logistic regression analyses were employed to identify the factors associated with WV, considering a significance level of p-value < 0.05. Results The study was conducted among 607 healthcare providers and support personnel across 10 public and private hospitals. The lifetime career, and one-year exposure to any form of WV was 414 (68.2%) [95% CI: (64.3-71.9%)] and 363 (59.8%) [95% CI: (55.8-63.7%)], respectively. Compared to other forms of WV, the majority of healthcare workers, 324 (53.4%) experienced verbal abuse within the past year, and a greater proportion, 85 (26.2%) became 'super alert' or vigilant and watchful following incidents of verbal abuse. Factors significantly linked to experiencing any form of WV in the previous 12 months were identified as follows: older age [AOR = 1.11 (1.06, 1.17)], working experience [AOR = 0.91 (0.86, 0.96)], having on-call responsibilities [AOR = 1.75 (1.17, 2.61)], and feeling adequately secure within health facility [AOR = 0.45 (0.26, 0.76)]. Conclusion There was high occurrence of WV, and verbal abuse was the most experienced form of WV. Age, work experience, on-call duties, and security within workplace were associated with exposure to WV. Facility-based interventions are urgently needed to curb the incidence of WV, especially verbal abuse.